Correspondability, water sustainability and sustainable development objective (SDG) 6 (Agroindustria, Sociedad y Ambiente, 2019)
In Venezuela, a large number of river channels are threatened by man-made aggressions from pollution, climate change, urban development and changes in nature, such as deforestation. Each one with a great specific impact, generally directly on the ecosystems and, in turn, on the water resources themselves. The objective of the essay is to build a theoretical approach to water co-responsibility and sustainability defined in the Sustainable Development Goal (SDG) 6 of the 2030 Agenda of the United Nations (UN) in the La Guamita I and II Parish Communities The Recreation of the San Fernando Municipality of the Apure State, being the Rio Apure, the tributary necessary for its subsistence. We used the postpositivist approach, and the phenomenological-hermeneutic method. The results allow us to notice scarce community co-responsibility and little homogeneity with the SDO6, so that reflections on such co-responsibility are produced from an interaction perspective, recommending the Communal Councils and authorities to synchronize self-management from the perspectives of SDG6.
Keywords: Communitarian Stewardship; Water Sustainability; ODS6